THE GROWTH OF SUPER VILLAGE CHICKEN BY FEEDING FERMENTED COFFEE SKIN WASTE IN RATION - Widnyana, I Gusti Ngurah Putu; Putri, Sania Anisa; Loliwu, Yan Alpius (Universitas Sintuwu Maroso, 2025)
This study aims to evaluate the effect of using fermented coffee skin waste in rations on the production performance of super kampung chickens, especially on body weight gain (PBB), feed consumption, and feed conversion. The material used was 68 super kampung chickens. The study used a Completely Randomized Design with 4 treatments and 4 replications with various levels of fermented coffee skin substitution in rations up to 20%. The variables observed were body weight gain, feed consumption and feed conversion. The results of the analysis showed that the use of fermented coffee skin waste had a significant effect (P <0.05) on PBB, feed consumption, and feed conversion. The highest average PBB was achieved in the treatment with 20% fermented coffee skin, which was 44.01 grams/head/day. The highest feed consumption was obtained at the 15% level with a value of 177.75 grams/head/day, while the best feed conversion was obtained at the 20% level, which was 3.96. Based on these results, the use of fermented coffee skin waste up to 20% in rations gave the best results on the growth efficiency of super kampung chickens.